2010
DOI: 10.1111/j.1748-5827.2010.00967.x
|View full text |Cite
|
Sign up to set email alerts
|

Saliva crystallisation as a means of determining optimal mating time in bitches

Abstract: This test could be used to complement other methods of determining the fertile period in bitches, but its potential capacity remains to be demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…It is composed of fine and very fine sand, with insertions, at different heights, of various shell levels of variable thickness. This sand sheet had been interpreted differently by previous authors: its granulometry, morphology and orientation parallel to the coast made Fernández-Palacios et al (1988) think that it was formerly a coastal aeolian sheet, while Zazo et al (1994) considered it a former spit bar, abandoned at present, which formed part of the barrier-island system located to the south of the mouth of the Guadalete river. Given the character of the deposit, fine and very fine sand, and its position on a barrier-island system, thinking that it is a former sand dune deposit is one of the easiest hypotheses to accept.…”
Section: Discussionmentioning
confidence: 99%
“…It is composed of fine and very fine sand, with insertions, at different heights, of various shell levels of variable thickness. This sand sheet had been interpreted differently by previous authors: its granulometry, morphology and orientation parallel to the coast made Fernández-Palacios et al (1988) think that it was formerly a coastal aeolian sheet, while Zazo et al (1994) considered it a former spit bar, abandoned at present, which formed part of the barrier-island system located to the south of the mouth of the Guadalete river. Given the character of the deposit, fine and very fine sand, and its position on a barrier-island system, thinking that it is a former sand dune deposit is one of the easiest hypotheses to accept.…”
Section: Discussionmentioning
confidence: 99%
“…However, progesterone suppresses the crystallization (MacDonald 1969, Linford 1974. Saliva crystallization was mainly studied in women (Kullander and Sonesson 1965;Berardono et al 1993) and we noticed only two studies focused on saliva crystallization in animalsin beagle bitches (Pardo-Carmona et al 2010) and camels (Camelus bactrianus) (Haberová 2010).…”
Section: Introductionmentioning
confidence: 93%
“…Obtaining of saliva is very simple and it can be performed by a breeder. Crystallization, also called ferning or arborisation, was described in vaginal mucus (Noonan et al 1975), nasal mucus (Peterson 1984), saliva (Pardo-Carmona et al 2010), tears (Golding and Brennan 1989), milk or colostrum (Zondek and Rozin 1954). The typical fern crystallization is distinctive near the peak of follicular activity and around ovulation time when oestrogens predominate.…”
Section: Introductionmentioning
confidence: 99%
“…Other methods has been proposed to monitor the bitch oestrous cycle, such as serial reading of the electrical resistance of the vaginal mucus around the time of ovulation, using probes inserted into the vagina during the heat period (Fontbonne, 2008), or the crystallization patterns in anterior vaginal fluids (England & Allen, 1989) or in saliva (Pardo-Carmona et al, 2010), which have been found up not to present an acceptable reliabily in the identification of the canine ovulation. …”
Section: Proposed Alternative Methodsmentioning
confidence: 99%